Influence of Out-of-School Experiences on Interest in Science of Secondary School Students in Kerala - Gafoor, Dr K. Abdul (INDIAN EDUCATIONAL REVIEW, 2012)
Influence of out-of-school experiences on interest in science and such experiences which are significantly contributive to interest are studied on a representative sample of grades 8-9 students of Kozhikode district. Locale but not gender difference exists in extent of interest. Over 40 per cent variance in science interest is attributable to out-of-school experiences. Observation and visits influence interest in science above collection and activity. Influence of common place life experiences among rural students and of structured, organised and planned experiences among urban students were evidenced. Among rural students influence from physical science related experiences is stronger. In urban sample, influence of visits and collections is more and that of activity mainly of physical sciences is less. Experimental experiences were found inconsequential on student interest. Implications for science curricula, instruction, textbooks and support facilities, teacher preparation, assessment and research are added.